Just wanted to add that you don't have to distribute first. It's also fine to divide both sides by 6, getting `h-4=0.` Then adding 4 to both sides gives `h=4.`

The equation 6(h - 4) = 0 has to be solved.

6(h - 4) = 0

=> h = 4

**The solution of 6(h - 4) = 0 is h = 4**

Your original equation is 6(h-4)=0

The first step is to use the distributive property. In doing so, we distribute the 6 in the following way:

** 6***h -

**4 = 0**

*6**Next, we simplify the multiplication as follows:

6h - 24 = 0

Now remember our goal is to get h by itself. So first, we need to get rid of any subtraction or addition by doing the following:

6h - 24 ** + 24** = 0

*+ 24**remember, we need to keep the equation balanced, so when we add or subtract from one side, we need to do it to the other side too!

Now we simplify and get:

6h = 24

To get the h by itself, we must get rid of the multiplication by 6. The opposite of multiplication is division, so we will want to divide. Also, since we are going to divide on one side, in order to keep it balanced we must divide on the other side too! We have the following:

6h ** / 6** = 24

*/ 6*Simplifying, we have:

** 6/6** h = 4

and 6/6 simplifies to equal 1 so we have:

1h = 4

thus, h=4

Remember because it is an equation, both sides must be equal in this case that is 0. Following the rules of equations, you must complete the parenthetical first.

6(h-4) = 0

6h - 24 = 0

6h = 24

h = 24/6

h = 4

check the answer: 6(4-4) = 0

6(0) = 0

0 = 0

first you take 6 and distribute it to the h and -4. they you multiply the 6 and h which is 6h. then you multiply the 6 and -4 which is -24 so you have 6h-24=0. then you add 24 to 0 which is 24. they take 6h=24 and divde 6 on both sides. your answer would be h=4.

Okay so as you can see the quation has brackets, which you can expand.

So, *6(h-4)=0*

Is, *6h-24=0* **exapnded**.

You need the letters on one side, and numbers on the other to solve for *h.*

So you now have, *6h=+24* **(now positive because taken to the other side).**

Now you have to divide 6 from both sides because we don't need it and we want to get *h=something.*

So, *6h=24*

* --- ---*

*6 6**6* from *6h* get's cancelled and you end up with *24* which is *4*.

*---*

*6*

So, **h=4**

To solve 6( h - 4 ) = 0 first distribute the equation on the left

By distributing, the equation would be

**6h -24 = 0** Now you have to add 24 on both sides

By adding 24 on both sides your equation would be

**6h = 24** now divide 6 on both sides

by dividing 6 on both sides you'll get

**h = 4** which is your answer

6(h - 4) = 0

You're lucky. They even factored it for you!

Remember this property of multiplication :

ab = 0 so long as either a = 0, b = 0 or a and b both = 0.

In this case, a = 6 and b= h - 4.

We know that 6 can never equal zero so must turn to the h - 4 term. We need to make

h - 4 = 0

Solve for h:

h = 4

6(h - 4) = 0

Distribute it so the h is in both parts of the equation and solve

6h-24=0

move 24 on the other side

6h=24 and divide it by 6

h=4